2012
DOI: 10.1177/0017896912446550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of education sessions of a structured school eye screening programme on Indian schoolteachers’ knowledge and responsibility for children’s eye health

Abstract: Objective: To evaluate the effect of education sessions on Indian schoolteacher awareness of childhood eye health issues, responsibility for children’s eye health, and successful participation in a teacher-led eye screening health intervention programme in primary schools aimed at addressing avoidable childhood blindness in India. Design: Quantitative study, pre-intervention and post-intervention surveys and questionnaires. Setting: One hundred and four government-employed schoolteachers in primary schools of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“… 19 – 66 Identified articles were from 13 countries spanning five World Health Organization (WHO) Regions including Africa (eight studies), the Americas (10 studies), the Eastern Mediterranean (one study), South-East Asia (18 studies) and the Western Pacific (11 studies). Identified articles comprised 19 school-based eye-care programme evaluations, 19 – 33 , 62 – 64 , 66 16 studies investigating spectacle compliance associations, 34 48 , 65 eight studies exploring the quality of various eye-care screening personnel, 49 56 four studies evaluating the effectiveness of eye health promotion, 57 60 and one study that included both spectacle compliance and the quality of screening personnel 61 . When appraised for quality, 15 we classified 18 studies as being of high quality, 20 as medium quality and 10 as low quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 19 – 66 Identified articles were from 13 countries spanning five World Health Organization (WHO) Regions including Africa (eight studies), the Americas (10 studies), the Eastern Mediterranean (one study), South-East Asia (18 studies) and the Western Pacific (11 studies). Identified articles comprised 19 school-based eye-care programme evaluations, 19 – 33 , 62 – 64 , 66 16 studies investigating spectacle compliance associations, 34 48 , 65 eight studies exploring the quality of various eye-care screening personnel, 49 56 four studies evaluating the effectiveness of eye health promotion, 57 60 and one study that included both spectacle compliance and the quality of screening personnel 61 . When appraised for quality, 15 we classified 18 studies as being of high quality, 20 as medium quality and 10 as low quality.…”
Section: Resultsmentioning
confidence: 99%
“…As the availability of eye-care specialists can be limited in school settings, particularly in low- and middle-income countries, studies have investigated the use of teachers, nurses, certified medical assistants and key informants for the provision of screening and basic eye-care for children 20 , 21 , 29 , 51 54 , 56 , 58 , 60 , 62 . Several studies found that training teachers in vision screening enabled the provision of a good-quality 51 , 53 , 56 and cost–effective service, 53 while facilitating the opportunity to motivate spectacle use among students 54 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Using school teachers to detect pupil's vision related problems was first documented in 1975; however, since then many studies have documented the reliability and effectiveness of teacher's involvement in screening. 12,13,14,15,16,17,18 The advantages of VA testing using logarithm of minimum angle of resolution (logMAR) acuity measurement charts, over the use of Snellen charts, are well known. LogMAR acuity measurement utilizes the letter-by-letter scoring principle in contrast to Snellen where the acuity will be obtained by the line-by-line scoring method.…”
Section: Discussionmentioning
confidence: 99%